أثر التدفقات المالية الدولية على التنمية الاقتصادية في الجزائر دراسة قياسية باستخدام نموذج ARDL خلال الفترة 1980 – 2021 : The impact of international financial flows on economic development in Algeria An econometric study using the ARDL model during the period (1980-2021) - بن العايب عادل عبد الباسط; بودالي بلقاسم (Journal of North African Economies, 2025)
This study aims to measure the impact of international financial flows on economic development in the long run in Algeria for the period (1980-2021), using the Autoregressive Lagging Distributed Time Lag (ARDL) model. The study results concluded that there is a long-term equilibrium relationship between financial flows. International and economic development, as the results of the assessment showed that international financial flows (FDI, FPI, ODA, REM) have a positive and significant impact on economic development (GDPH) in Algeria in the short and long term; Except for the total external debt stock (EXTDS), which has a negative and significant impact on economic development ( GDPH)